Combined Associations of Liver Enzymes and Obesity With Diabetes Mellitus Prevalence: The Tohoku Medical Megabank Community-based Cohort Study - Fumi Itabashi; Takumi Hirata; Mana Kogure; Akira Narita; Naho Tsuchiya; Tomohiro Nakamura; Naoki Nakaya; Ryohei Sasaki; Nobuyuki Takanashi; Kiyomi Sakata; Kozo Tanno; Junichi Sugawara; et al. (Journal of Epidemiology, 2022)
Background: Alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) are enzymes associated with diabetes mellitus (DM) prevalence. However, limited information is available regarding the association of liver enzymes and DM consistently present in obese and non-obese individuals. We examined whether the combination of ALT and GGT enzymes is associated with the prevalence of DM, regardless of obesity, in a general Japanese population. Methods: We conducted a cross-sectional study of 62,786 participants aged ≥20 years who lived in Miyagi and Iwate, Japan. We divided all the participants into eight groups according to the ALT level (low: <30 IU/L and high: ≥30 IU/L), GGT level (low: <50 IU/L and high: ≥50 IU/L), and the presence of obesity. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) using multivariable logistic regression analysis, adjusting for potential confounders, to determine associations of the combination of ALT and GGT levels and obesity with DM prevalence. Results: Overall, 6,008 participants (9.6%) had DM. Compared to non-obese individuals with low ALT and GGT levels, the participants with high ALT and GGT levels had high ORs for DM in both obese (OR 4.06; 95% CI, 3.61–4.56) and non-obese groups (OR 2.19; 95% CI, 1.89–2.52). The obese group had high ORs for DM, even at low ALT and GGT levels. Conclusion: High ALT and GGT levels are associated with DM prevalence in obese and non-obese participants. This finding suggests that correcting ALT and GGT levels and controlling obesity are important for the prevention of DM.